2013
DOI: 10.1177/1534734613502034
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Effectiveness of Two Compression Stocking Treatments on Venous Leg Ulcer Recurrence

Abstract: Venous leg ulcers affect up to 3% of people aged 65 years and older, present significant pain and suffering, and are associated with long episodes of health care. These chronic wounds recur at rates of up to 69%. A double blind randomized controlled trial was conducted in a home nursing setting in Victoria, Australia to compare the effectiveness of a 23 to 32 mm Hg (moderate) and a 34 to 46 mm Hg (high) compression stocking treatment on venous ulcer recurrence. Participants (n = 100) were monitored for 26 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 17 publications
4
62
1
1
Order By: Relevance
“…In most studies, recurrence was defined as a new ulcer developing after the patient healed and could be on the other leg or in another location. Some measured the number of people with a current VLU who reported a previous VLU; this ranged from “half”, assumed to be 50.0%, to 81.7% . Other studies measured recurrence after healing within 5 weeks: 23.1%; at 3 months, ranging from 5.6% to 36.0%; at 6 months: 73.5%; and at 12 months, ranging from 16.7% to 20.0% .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most studies, recurrence was defined as a new ulcer developing after the patient healed and could be on the other leg or in another location. Some measured the number of people with a current VLU who reported a previous VLU; this ranged from “half”, assumed to be 50.0%, to 81.7% . Other studies measured recurrence after healing within 5 weeks: 23.1%; at 3 months, ranging from 5.6% to 36.0%; at 6 months: 73.5%; and at 12 months, ranging from 16.7% to 20.0% .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies measured recurrence after healing within 5 weeks: 23.1%; at 3 months, ranging from 5.6% to 36.0%; at 6 months: 73.5%; and at 12 months, ranging from 16.7% to 20.0% . Other studies reported a median time to recurrence ranging from 11.1 to 63.0 weeks …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Kapp et al . ). Other actions include exercise and leg elevation (Flaherty ), use of moisturisers (Finlayson et al .…”
Section: Introductionmentioning
confidence: 97%
“…This data is similar to other authors' findings, who obtained an annual prevalence of varicose ulcer corresponding to 1.69% among the elderly. This health problem is considered significant for these people (15,16) and for the health sector, considering that the life expectancy is rising and that, in the next 40 years, the number of elderly people is expected to double. (17) Although no association was found between the instruction level and relapse or the emergence of a new ulcer, patients with a lower level of instruction (illiterate and functional illiterate) were predominant in terms of relapse and the development of a new injury, while patients with secondary and higher education did not present such events.…”
Section: Discussionmentioning
confidence: 99%